THE ROLE OF ISLAMIC PHILANTHROPY AND ORGANIZATIONAL COMPETENCE IN FOSTERING STUDENT COMMUNITY RESILIENCE: LESSONS FROM BAZNAS - Rahmat, Wahyudi; Tiawati, Refa Lina; Cesaria, Anna; Azri, Harizqi; Rahmad, Hari Adi; Yuhendri, Rival (Bhandar: Harvesting Community Service in Asia, 2025)
This community service article advocates integrating structured Islamic philanthropy, exemplified by the National Amil Zakat Agency (BAZNAS), into Muslim student communities at Universitas PGRI Sumatera Barat (UPGRISBA) and Universitas Bung Hatta (UBH). Indonesia, prone to recurrent natural disasters, requires sustainable preparedness systems. In this context, BAZNAS serves as a strategic quasi-state actor that bridges religious duty and bureaucratic professionalism. The study of BAZNAS’s discourse, as analyzed through Critical Discourse Analysis (CDA), reveals a model where institutional legitimacy is constructed through three synergistic layers: Syariah legitimacy (via MUI Fatwa 66/2022), technocratic-managerial legitimacy (through ISO 9001:2015 and WTP audit opinions), and political legitimacy (via endorsements from state officials, including the Vice President). This multi-layered approach transforms Zakat from traditional charity into a modern instrument of disaster governance and social resilience. This community service intervention aims to transfer this BAZNAS model of